Π–hole interactions at work: crystal engineering with nitro-derivatives. Issue 14 (20th March 2017) - Bauzá, Antonio; Sharko, Anastasiya V.; Senchyk, Ganna A.; Rusanov, Eduard B.; Frontera, Antonio; Domasevitch, Kostiantyn V.
Abstract : A series of dinitrodiene derivatives present crucial π–hole interactions involving the nitro group as a π–hole donor in the solid state. Abstract : In this manuscript, we report the design, synthesis and X-ray characterization of nitrodiene derivatives that present crucial π–hole interactions involving the nitro group as a π–hole donor. The solid state structures of 1, 4-dinitro-1, 3-butadiene (1 ), its co-crystal1 ·Diox, and homologous 1, 4-dinitro-1, 3-pentadiene (2 ) and 2, 4-dinitro-2, 4-hexadiene (3 ) feature competition of lone pair–π–hole interactions with common weak CH⋯O bonding and gradually increased role of the NO2 ⋯NO2 interactions. Regular evolution of the supramolecular patterns (1 to3 ) results in generation of an unprecedented 3D non-covalent framework in3 that is controlled exclusively by short π–hole contacts (O⋯N = 2.9615(18), 3.1304(18) Å). These findings complement the results of high level ab initio calculations (MP2/def2-TZVP) and unite theory and experiment, thus supporting the functional relevance of this novel π–hole interaction.